Mango Breeding in India - Past and Future - M R Dinesh (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2016)
The mango (Mangifera indica L.) is one of the most important tropical fruits of India in which improvement has been attempted since the early 20th Century. The species, M. indica, having originated in India, has a large diversity within the country. Extensive surveys have located several wild species of importance, many of them figuring in the IUCN Red List. Conservation and evaluation of these species, as well as the large seedling diversity, needs attention as these could be a source for important traits. Strategies of in situ, ex situ and 'onfarm' conservation should from a priority at this juncture. Hybridization has resulted in several hybrids. Widening of genetic base in polyembryonic varieties and identification of zygotic embryos through markers is the need of the hour for utilization in breeding programmes. Although several of these have not become popular, they can be very well used as pre-breeding lines. Use of molecular markers for selection will greatly reduce time taken for developing improved varieties. Strategies other than hybridization, viz., selection among open-pollinated progenies, should be adopted for identifying better recombinants, as, a large number of progenies are available in this method.